1999
DOI: 10.1159/000023449
|View full text |Cite
|
Sign up to set email alerts
|

Serum Osteocalcin and Insulin-Like Growth Factor I Levels in Children with Congenital Adrenal Hyperplasia

Abstract: Patients with the virilizing forms of congenital adrenal hyperplasia (CAH) need a life-long glucocorticoid replacement therapy and also an additional mineralocorticoid replacement in cases with the salt-wasting form of the disease. Glucocorticoids are reported to decrease the serum osteocalcin levels and to inhibit the effects of insulin-like growth factor I (IGF-I). To collect data on the age related patterns of osteocalcin and IGF-I production in patients with CAH, measurements of these compounds have been c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 37 publications
(28 reference statements)
2
7
0
Order By: Relevance
“…There was only a tendency for NC patients to have not significantly higher osteocalcin levels, reflecting either a better osteoblast function following a lower corticosteroid dosage or perhaps only a different age. Our results on bone markers of neoformation and resorption are in agreement with those of Girgis and Winter [4], while other authors found lower than normal osteocalcin [22, 23, 24]and NTx [24]levels in their patients. There is no clear explanation for these different findings.…”
Section: Discussionsupporting
confidence: 93%
“…There was only a tendency for NC patients to have not significantly higher osteocalcin levels, reflecting either a better osteoblast function following a lower corticosteroid dosage or perhaps only a different age. Our results on bone markers of neoformation and resorption are in agreement with those of Girgis and Winter [4], while other authors found lower than normal osteocalcin [22, 23, 24]and NTx [24]levels in their patients. There is no clear explanation for these different findings.…”
Section: Discussionsupporting
confidence: 93%
“…Although the majority of previous studies in CAH have demonstrated normal BMD and BMC, consistent with our findings, the literature suggests that children and adults with this diagnosis have depressed bone turnover, reflected by altered patterns of bone turnover markers 31,32 . Our bone turnover data support the theory that there is an uncoupling of bone turnover in patients with CAH, with low osteocalcin values and elevated N-telopeptide levels seen in the majority of participants.…”
Section: Discussionsupporting
confidence: 89%
“…The growth hormone IGF-I axis was not responsible for the loss in final height potential during puberty as normal to increased serum levels of IGF-I during puberty in treated CAH patients were found. 33 In non-salt wasting patients, females were diagnosed earlier than NSW males with a less advantaged bone age and better height prognosis. In males, loss of final height was more pronounced because of late diagnosis.…”
Section: Discussionmentioning
confidence: 99%